P389Role of truncated plakophilin-2 in arrhythmogenic right ventricular cardiomyopathy. (15th July 2014) - Alcalde, M; Campuzano, O; Beltran-Alvarez, P; Pagans, S; Verges, M; Brugada, R
Abstract: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a rare cardiac disease characterized by fibrofatty replacement of the right ventricular myocardium, which may cause ventricular arrhythmias and sudden cardiac death (SCD). Mutations in genes encoding desmosome proteins have been associated with ARVC: plakophilin-2 (PKP2), desmoplakin (DSP), desmocolin-2 (DSC2), desmoglein-2 (DSG2) and plakoglobin (PG). Plakophilin-2 (PKP2) is the most prevalent gene associated with ARVC, especially stop-gained mutations, which lead to truncated PKP2 (PKP2TR). Our recent genetic studies have shown that PKP2TR is associated to a later age of ARVC onset (37 years old) compared to missense carriers (27 years old). This raised an alternative hypothesis as to the pathogenicity of missense and truncated proteins, and their role in phenotype. We hypothesize that PKP2TR is associated with trafficking to the plasma membrane, which can be compensated by the normal allele; while missense variations may act through a dominant negative effect, disrupting the function of the wild type protein since they are mostly incorporated to desmosome. To explore this hypothesis, we performed an in vitro study with the three following aims: (1) to examine the subcellular location of PKP2TR forms in the in HL-1 cardiac-like cells, (2) how PKP2TR length affect to their proper traffic to plasma membrane and (3) PKP2TR effect on desmosome assembly. Based on mutations associated to ARVC in our genetic study, we selected four PKP2TR versions (at amino acids 91, 412, 637 and 734), which were transiently co-transfected in HL-1 cells with major desmosome proteins (DSP, DSC2, DSG2 and PG). We observed that these PKP2TR forms are not localized efficiently to the plasma membrane; PKP2TR-91 remained diffuse in the cytoplasm; PKP2TR-412 was retained in the endoplasmic reticulum displaying a dotted pattern. In contrast PKP2TR-637 and PKP2TR-734 were only partially located to the plasma membrane with a major fraction still cytosolic. We also observed that all PKP2TR caused deficient localization of other desmosome proteins, especially DSP, which requires PKP2 for its proper trafficking to the plasma membrane. Thus, these data suggest that the degree of the truncation in PKP2 does not correlate with a clear effect in desmosome assembly. Results clearly show that PKP2TR forms are not efficiently incorporated to the plasma membrane, and they affect desmosome assembly. These data favour the idea that PKP2TR may be associated to trafficking defect, while missense mutations may act in a dominant negative way disrupting function of the wild-type protein.